The impact of monetary union on trade prices - Daria Taglioni; Robert Anderton; Richard E. Baldwin (European Central Bank (ECB), 2003)
Two seemingly unconnected empirical results suggest an intriguing mechanism. First, economic integration helps harmonize prices internationally, with trade being the primary channel (Rogoff 1996, Goldberg and Knetter 1997). Second, monetary union may greatly increase the amount of trade among members (Rose 2001). Putting these together, we see that formation of a monetary union may induce changes that help harmonise inflation rates. The effect might be large if the elimination of exchange rate volatility simultaneously leads to a large increase in intra-union trade and a big increase in the speed at which price shocks are transmitted across members' goods markets. This paper investigates part of this mechanism and finds that monetary union may indeed result in faster cross-border transmission of price movements via the import and export price channel which, in turn, would tend to homogenise price movements across the member countries of a monetary union.
Keywords: D40; F15; F31; 330; Exchange rate volatility; harmonisation of price movements; market segmentation; monetary union; no-arbitrage bands